2013
DOI: 10.1007/s11914-013-0141-8
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of the Hip and Spine Based on Quantitative Computed Tomography

Abstract: Quantitative computed tomography (QCT) provides three-dimensional information about bone geometry and the spatial distribution of bone mineral. Images obtained with QCT can be used to create finite element models, which offer the ability to analyze bone strength and the distribution of mechanical stress and physical deformation. This approach can be used to investigate different mechanical loading scenarios (stance and fall configurations at the hip, for example) and to estimate whole bone strength and the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…A recent report reviewed the principles of the CT-based FE method and its application in the hip and spine. 11 In this paper, we aim to synthesize three recent validation experiments performed in our laboratory for patient-specific modeling of three skeletal sites at high risk of osteoporotic fractures: the distal radius, the vertebral body and the proximal femur. In particular, we quantify the predictive power of the voxel-based FE methodology for the image resolution available in vivo and compare it with the current densitometric surrogates of bone strength, bone mineral content (BMC) and areal bone mineral density (aBMD), for each anatomical site.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report reviewed the principles of the CT-based FE method and its application in the hip and spine. 11 In this paper, we aim to synthesize three recent validation experiments performed in our laboratory for patient-specific modeling of three skeletal sites at high risk of osteoporotic fractures: the distal radius, the vertebral body and the proximal femur. In particular, we quantify the predictive power of the voxel-based FE methodology for the image resolution available in vivo and compare it with the current densitometric surrogates of bone strength, bone mineral content (BMC) and areal bone mineral density (aBMD), for each anatomical site.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative computed tomography (QCT)‐based finite element (FE) models are a promising tool for fracture risk assessment. These models can accommodate parameters related to the lesion, but can also cover additional aspects that play an important role in the assessment of the risk of fracture, such as the bone geometry, bone quality, and the daily loads applied to the bone . For example, the work by Whyne et al and Tschirhart et al studied the influence of tumor growth and loading scenario on precursors of burst fractures (e.g., load induced canal narrowing and vertebral bulge).…”
mentioning
confidence: 99%
“…Theoretically, FEA should be the most powerful tool, as it integrates most of the biomechanical variables and it is based on well-established engineering mechanics theories and principles. Image-based FEA has advanced our understanding of bone biology and etiology of osteoporotic fracture [226][227][228]. In vitro studies have demonstrated that QCTbased FEA significantly improves the prediction of bone strength than densitometric measures [225,229].…”
Section: Links Between Biomechanical Variables and Clinical Risk Factorsmentioning
confidence: 99%